Knowledge, Attitude and Practice Among Parents Of Children With Otitis Media Attending A Tertiary Care Hospital - A Cross Sectional Study - Asaithamby, Umarani; Velayutham, Prabu; Kangadaran, Hemabalan; Thangamuthu, Gautham; Vasudevan, Kiruthika; Loganathan, Abinaya (Journal of Neonatal Surgery, 2025)
Introduction: Otitis media is one of the common ENT problem encountered in day-to-day practices. It is one of the significant causes of hearing loss in children. Studies have shown that about 11% of the population suffered from acute otitis media, whereas 5% of the patients suffered from chronic otitis media. The consequences of otitis media in untreated children were found to be debilitating. So, proper diagnosis and treatment were needed to prevent the complication, and adequate knowledge about the disease was needed for the parents. The aim of the study was to assess parents' knowledge, attitudes, and practices regarding children with otitis media in a tertiary care hospital in Puducherry. Methods: The study was conducted among parents attending the hospital with their children in a tertiary care centre in Puducherry. The study was conducted between April 2024 and June 2024. A semi-structured questionnaire was administered to all the study participants. Results: A total of 140 parents participated in the study. In the study, most parents know the symptoms and causes of otitis media. The study showed that 69.3% of the parents had good knowledge, 71.4% had a positive attitude, and 75% had good practices concerning otitis media and the knowledge score was significantly associated with age (p-0.042), gender (p-<0.001), locality (p-0.001), occupation (p-<0.001) and the number of children (p-<0.001) and attitude score was associated with age (p-<0.001), gender (p-0.010), locality (p-<0.001), occupation (p-0.001), socio-economic status (p-0.021) and number of children (p-0.036) and the practice score significant association with age (p<0.001), gender (p<0.001), occupation (p-0.008), socioeconomic status (p-0.013) and number of children (p-0.009). Conclusion: The knowledge attitude and practice regarding the otitis media were found to be adequate among the parents. The study recommends that parents should be encouraged to have an annual health check-up visit with their children to find out the condition at an earlier stage and treat them accordingly.